Violencia Laboral contra Mujeres Campesinas de la parroquia San Lucas, cantón Loja - Ecuador - Ortega Jaramillo, Karina Patricia (2022)
Labor violence is considered to be any act that hurts or harms, evidencing the various expressions, which threaten the integrity of peasant women, who are in charge of tilling and cultivating the land, playing an important role in the changes and advances of the economy of an entire country; The methodology used in this article is of a quantitative type, through an exploratory and descriptive epistemological approach, of a cross-sectional cohort, through the application of the survey technique and the instrument of a questionnaire, addressed to 65 peasant women of the San Lucas parish, Loja canton – Ecuador; its objective was to determine workplace violence; In the results obtained, their high levels of this social phenomenon were evidenced, the discomfort they feel before the treatment received in their workplaces, added the shouts, humiliations and rudeness received; the lack of an inappropriate work environment generates wrong behavior within their homes, which causes discomfort, conflicts and poor communication in their intra-family relationships; 23% of rural women have felt uncomfortable with the treatment received at work and 40% state that the violence received negatively affects their homes;